EFFECT OF BULLYING BEHAVIOR AMONG UNIVERSITY STUDENTS IN FAISALABAD - Fatiha Rehman; Faiqa Mukhtar; Tayyba Naeem; Dr. Madiha Naz; Dr. Nouman Khaliq; Jaffar Hussain (International Journal of Contemporary Issues in Social Sciences, 2024)
Bullying has been defined as purposeful and repetitive abuse of another individual. It could be social, psychological, physical, or verbal. It could take place online or in person. It may be evident to others or concealed. The study intended to explore the impact of bullying behavior on academic achievement among university students in Faisalabad. Students who are bullied struggle to follow or focus on their studies for a variety of reasons. These students may also pass up opportunities to communicate with peers or participate in university activities. When harassed students are in class, they often become distracted. For gathering data, a multistage sampling technique was used. In the first phase, two universities were randomly picked from Faisalabad. Using purposive sampling approaches, 50 respondents from each university were selected in the second round. The data was collected using a carefully planned interview schedule. The data showed that bullying has a considerable negative impact on pupils’ academic achievement. Bullying and university students’ academic progress were linked. Bullying has detrimental psychological, emotional, mental, and physical consequences for students, which can lead to confidence and health difficulties. To eliminate bullying behavior in institutions, administrators and teachers must develop bullying prevention programs.